From Social Networks to Publishing Platforms: A Review of the History and Scholarship of Academic Social Network Sites - Jordan, Katy (Frontiers in Digital Humanities, 2019)
Social network sites enable people to easily connect to and communicate with others. Following the success of generic platforms such as Facebook, a variety of online services launched during the mid 2000s in order to bring the benefits of online social networking to an academic audience. However, it is not clear whether these academic social network sites (ASNS) are primarily aligned with social networking or alternative publishing, and functionalities continue to change. Now ten years since the launch of the three main platforms which currently lead the market (Academia.edu, ResearchGate, and Mendeley), it is timely to review how and why ASNS are used. This paper discusses the history and definition of ASNS, before providing a comprehensive review of the empirical research related to ASNS to-date. Five main themes within the research literature are identified, including: the relationship of the platforms to Open Access publishing; metrics; interactions with others through the platforms; platform demographics and social structure; and user perspectives. Discussing the themes in the research both provides academics with a greater understanding of what ASNS can do and their limitations, and identifies gaps in the literature which would be valuable to explore in future research.